Novel mutations in the SGCA gene in unrelated Vietnamese patients with limb-girdle muscular dystrophies disease - Chung Tran, Nam; Lien, Nguyen Thi Kim; Ta, Thanh Dat; Nguyen, Van Hung; Tran, Huy Thinh; Van Tung, Nguyen; Xuan, Nguyen Thi; Huy Hoang, Nguyen; Tran, Van Khanh (Frontiers in Genetics, 2023)
Background: Limb-girdle muscular dystrophy (LGMD) is a group of inherited neuromuscular disorders characterized by atrophy and weakness in the shoulders and hips.Over 30 subtypes have been described in five dominant (LGMD type 1 or LGMDD) and 27 recessive (LGMD type 2 or LGMDR). Each subtype involves a mutation in a single gene and has high heterogeneity in age of onset, expression, progression, and prognosis. In addition, the lack of understanding of the disease and the vague, nonspecific symptoms ofLGMD subtypes make diagnosis difficult. Even as next-generation sequencing (NGS) genetic testing has become commonplace, some patients remain undiagnosed for many years.Methods: To identify LGMD-associated mutations, Targeted sequencing was performed in the patients and Sanger sequencing was performed in patients and family members. The in silico analysis tools such as Fathmm, M-CAP, Mutation Taster, PolyPhen 2, PROVEAN, REVEL, SIFT, MaxEntScan, Spliceailookup, Human Splicing Finder, NetGene2, and Fruitfly were used to predict the influence of the novel mutations. The pathogenicity of the mutation was interpreted according to the ACMG guidelines.Results: In this study, six patients from four different Vietnamese families were collected for genetic analysis at